Composite lithium supplement and preparation method thereof, positive electrode sheet, battery and electric device
Patent Information
- Application Number
- CN202611164700.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-20
AI Technical Summary
牺牲型添加剂中,富锂过渡金属氧化物(如Li6CoO4)理论补锂容量高、分解电位低,是代表性正极补锂添加剂,但其实际应用存在明显不足:富锂程度高、表面碱性强,易与空气中水分和CO2反应生成LiOH、Li2CO3,导致材料吸湿、补锂容量下降、浆料不稳定;此外,该材料在首次脱锂过程中还伴随结构重排和副反应,易引发产气、界面副反应和应力集中等问题
[0013]本申请第二方面,提供了一种制备前面所述的复合补锂剂的方法。根据本申请的实施例,该方法包括:将锂源和钴源按化学计量比混合,在惰性气氛下进行第一烧结,得到第一烧结产物;将所述第一烧结产物与碳源混合,在惰性气氛或还原气氛下进行第二烧结,以在所述第一烧结产物表面形成第一包覆层,得到第二烧结产物;将所述第二烧结产物与金属氧化物源混合,在惰性气氛下进行第三烧结,以在所述第二烧结产物表面形成第二包覆层,得到复合补锂剂;其中,所述第二烧结包括第一保温阶段和第二保温阶段,其中,第一保温阶段的保温温度为300℃~500℃;第二保温阶段的保温温度为550℃~700℃。该方法中,通过分段烧结的第二烧结可以诱导第一烧结产物表层发生受控还原并原位生成钴单质,得到综合性能较佳的复合补锂剂;且操作简单、方便,与现有工艺兼容性高,易于实现规模化生产,得到的复合补锂剂具有更高的补锂容量和化学稳定性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, specifically to composite lithium replenishing agents and their preparation methods, positive electrode sheets, batteries, and electrical devices. Background Technology
[0002] Lithium-ion batteries, with their high energy density and long cycle life, have been widely used in power batteries, consumer electronics, and energy storage power stations. However, lithium-ion batteries generally suffer from significant irreversible capacity loss during the first charge and discharge cycle, resulting in low initial coulombic efficiency and limited cycle life. Therefore, introducing additional active lithium sources to compensate for irreversible lithium loss has become an important technological approach. Sacrificial lithium replenishment additives can be directly incorporated into the slurry, releasing active lithium during the first charge and discharge cycle. They offer advantages such as simple processing, controllable lithium replenishment, and compatibility with existing manufacturing systems, making them more promising for industrialization. Among sacrificial additives, lithium-rich transition metal oxides (such as Li6CoO4) have high theoretical lithium replenishment capacity and low decomposition potential, making them representative cathode lithium replenishment additives. However, their practical applications have significant shortcomings: high lithium enrichment and strong surface alkalinity make them prone to reacting with moisture and CO2 in the air to generate LiOH and Li2CO3, leading to material hygroscopicity, decreased lithium replenishment capacity, and slurry instability. Furthermore, the material undergoes structural rearrangement and side reactions during the first delithiation process, easily causing problems such as gas generation, interfacial side reactions, and stress concentration. Therefore, the technology related to lithium-rich transition metal oxide lithium supplementation agents still needs improvement. Summary of the Invention
[0003] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention proposes a composite lithium replenishing agent and its preparation method, a positive electrode, a battery, and an electrical device. This composite lithium replenishing agent exhibits high specific charging capacity and excellent air stability.
[0004] In a first aspect, this application provides a composite lithium replenishing agent. According to embodiments of this application, the composite lithium replenishing agent comprises: a core, said core comprising Li a CoO4 and elemental cobalt, 5.7 ≤ a ≤ 6.3; a coating layer, the coating layer covering at least a portion of the surface of the core, and including a first coating layer and a second coating layer, the first coating layer being located between the core and the second coating layer; the first coating layer is a carbon coating layer, and the second coating layer includes a metal oxide. This composite lithium replenisher has high specific capacity and excellent air stability, while being effectively compatible with current positive electrode processes.
[0005] According to an embodiment of this application, the concentration of cobalt gradually decreases in the direction from the core surface to the core center.
[0006] According to an embodiment of this application, the XRD pattern of the composite lithium supplement contains a first diffraction peak and a second diffraction peak. The 2θ of the first diffraction peak is located between 23.38° and 23.58°, and the 2θ of the second diffraction peak is located between 44.1° and 47.5°. The ratio of the peak intensity I1 of the first diffraction peak to the peak intensity I2 of the second diffraction peak is P1 = I2 / I1, and satisfies: 1.2% ≤ P1 ≤ 5%.
[0007] According to an embodiment of this application, P1 gradually decreases in the direction from the kernel surface to the kernel center.
[0008] According to embodiments of this application, the composite lithium supplement meets at least one of the following conditions: The mass ratio of the core to the first coating layer is 100:(1~4); The mass ratio of the core to the second coating layer is 100:(0.13~3.78).
[0009] According to embodiments of this application, the metal oxide includes Li m MO (m+n) / 2 M includes Al and / or Mn, 0 ≤ m ≤ 2, 2≤n≤4; Preferably, the metal oxide includes at least one of Al2O3, LiAlO2, MnO, Mn2O3, Mn3O4, MnO2, LiMnO2, Li2MnO3, and LiMn2O4.
[0010] According to an embodiment of this application, the XRD pattern of the composite lithium supplement contains a third diffraction peak, which is the strongest peak among the diffraction peaks with 2θ located between 21.2°~22.7°, 34.2°~35.7°, 44.9°~46.9°, 56.1°~67.7°, 15.0°~15.8°, 18.1°~18.9°, 31.6°~36.6°, and 39.8°~41.3°; the ratio of the peak intensity I3 of the third diffraction peak to the peak intensity I1 of the first diffraction peak is P2=I3 / I1, and satisfies: 0<P2≤3.5%.
[0011] According to embodiments of this application, the composite lithium supplement meets at least one of the following conditions: The coating coverage of the composite lithium supplement is 80%~95%; The particle size D of the composite lithium supplement v50 The thickness ranges from 6.0 μm to 16.0 μm, preferably from 7.0 μm to 14.0 μm; The specific surface area of the composite lithium supplement is 0.3 m². 2 / g~1.8 m2 / g, preferably 0.4 m 2 / g~1.5 m 2 / g; The compaction density of the composite lithium supplement is 1.7 g / cm³. 3 ~2.1 g / cm 3 The preferred value is 1.9 g / cm³. 3 ~2.0 g / cm 3 .
[0012] According to embodiments of this application, the composite lithium supplement meets at least one of the following conditions: The first-week charging specific capacity of the composite lithium replenisher is 800 mAh g. -1 ~950 mAh g -1 ; The composite lithium replenishing agent retains 80%~99% of its capacity after being placed for 4 hours at a temperature of 25℃±1℃ and a relative humidity of 15%±2%.
[0013] A second aspect of this application provides a method for preparing the aforementioned composite lithium supplement. According to an embodiment of this application, the method includes: mixing a lithium source and a cobalt source in a stoichiometric ratio, and performing a first sintering under an inert atmosphere to obtain a first sintered product; mixing the first sintered product with a carbon source, and performing a second sintering under an inert or reducing atmosphere to form a first coating layer on the surface of the first sintered product to obtain a second sintered product; mixing the second sintered product with a metal oxide source, and performing a third sintering under an inert atmosphere to form a second coating layer on the surface of the second sintered product to obtain a composite lithium supplement; wherein the second sintering includes a first holding stage and a second holding stage, wherein the holding temperature of the first holding stage is 300°C to 500°C; and the holding temperature of the second holding stage is 550°C to 700°C. In this method, the second sintering through segmented sintering can induce controlled reduction of the surface layer of the first sintering product and generate cobalt in situ, resulting in a composite lithium supplement with better overall performance. Moreover, the operation is simple and convenient, highly compatible with existing processes, and easy to achieve large-scale production. The resulting composite lithium supplement has higher lithium supplementation capacity and chemical stability.
[0014] According to embodiments of this application, the method satisfies at least one of the following conditions: The mixing is achieved through a high-frequency mixer or hummingbird resonance. The inert atmosphere includes at least one of nitrogen or argon; The temperature of the first sintering is 500℃~1000℃; The first sintering time is 8h~24h.
[0015] According to embodiments of this application, the method satisfies at least one of the following conditions: The heat preservation time for the first heat preservation stage is 1 hour to 3 hours; The heat preservation time for the second heat preservation stage is 4 to 8 hours.
[0016] According to embodiments of this application, the method satisfies at least one of the following conditions: The temperature of the third sintering is 300℃~700℃; The third sintering time is 5h~10h.
[0017] According to embodiments of this application, the method satisfies at least one of the following conditions: The lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, and lithium chloride; The cobalt source includes at least one of cobalt oxide and cobalt hydroxide; The molar ratio of lithium in the lithium source to cobalt in the cobalt source is 5.7:1 to 6.3:1; The carbon source includes at least one of acetylene black, carbon nanotubes, and Ketjen black. The metal oxide source includes at least one of an aluminum source and a manganese source, preferably the aluminum source includes Al2O3, and the manganese source includes at least one of MnO, Mn2O3, Mn3O4, and MnO2.
[0018] In a third aspect, this application provides a positive electrode sheet. According to embodiments of this application, the positive electrode sheet includes the aforementioned composite lithium replenishing agent. When used in a battery, this positive electrode sheet exhibits a high initial charge specific capacity and a long cycle life.
[0019] In a fourth aspect, this application provides a battery. According to embodiments of this application, the battery includes the aforementioned composite lithium replenishing agent or the aforementioned positive electrode sheet. This battery exhibits a high initial charge specific capacity and a long cycle life.
[0020] A fifth aspect of this application provides an electrical device. According to embodiments of this application, the electrical device includes the aforementioned composite lithium replenisher, the aforementioned positive electrode, or the aforementioned battery. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the structure of a lithium replenishing agent according to an embodiment of this application; Figure 2 This is the XRD pattern of the composite lithium supplement agent of Example 1 of this application; Figure 3 This is the first-week charge-discharge curve of the button cell battery in Embodiment 1 of this application. Detailed Implementation
[0022] The embodiments of the present invention are described in detail below. These embodiments are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0023] In a first aspect, this application provides a composite lithium supplement agent. According to embodiments of this application, referring to... Figure 1 The composite lithium supplement includes: a core 10, wherein the core 10 comprises Li a CoO411 and elemental cobalt 12, 5.7 ≤ a ≤ 6.3; a coating layer, the coating layer covering at least a portion of the surface of the core 10, and including a first coating layer 20 and a second coating layer 30, the first coating layer 20 being located between the core 10 and the second coating layer 30; the first coating layer 20 is a carbon coating layer, and the second coating layer 30 includes a metal oxide. This composite lithium replenisher has high specific capacity and excellent air stability, while being effectively compatible with current positive electrode processes.
[0024] Specifically, the first coating layer can synergistically construct a continuous electron transport network with the cobalt in the core, reducing the impedance of the core during the initial delithiation process. Simultaneously, the first coating layer reduces direct contact between highly active sites on the core surface and moisture, carbon dioxide, and the electrolyte in the air, mitigating interfacial side reactions. Thus, the first coating layer synergistically enhances the delithiation kinetics, active lithium release efficiency, storage stability, slurry processing compatibility, and electrode coating uniformity of the composite lithium replenisher. Further adding a second coating layer serves two purposes: firstly, it can consume or fix residual active lithium on the core surface, reducing the generation of residual alkalis such as LiOH and Li2CO3, thereby improving the slurry processing compatibility of the composite lithium replenisher and reducing subsequent gas generation; secondly, metal oxides (such as aluminum-based oxides) possess good chemical inertness and interfacial stabilizing properties, suppressing surface side reactions, and also have certain lithium-ion transport capabilities and structural compatibility with the cathode system (such as manganese-based oxides), which can buffer interfacial stress during the delithiation process to some extent. Therefore, the second coating layer and the first coating layer can form a composite interface structure of "conductive buffer layer and stable protective layer", which not only retains the promoting effect of the first coating layer on the lithium replenishment agent's delithiation kinetics and electron transport, but also improves the chemical stability of the outer surface. Consequently, the composite lithium replenishment agent has a high specific charge capacity and excellent air stability.
[0025] According to an embodiment of this application, the concentration of cobalt gradually decreases in the direction from the core surface to the core center. Thus, the first coating layer can synergistically construct a continuous electron transport network from the particle interior to the particle surface with the gradient-distributed cobalt in the core. Specifically, the cobalt content is higher near the outer surface of the core, enabling it to form a good conductive connection with the first coating layer and reducing the impedance of the core during the initial delithiation process; the cobalt content is relatively lower near the inner core, which helps reduce the occupation of the inert metal relative to the lithium-rich active phase, thereby preserving the high lithium replenishment capacity of the core body. Furthermore, the gradient-distributed cobalt can simultaneously enhance surface conductivity and maintain internal capacity, promoting the full release of active lithium from the core interior to the outside, mitigating stress concentration during the initial delithiation process, and reducing the risk of localized over-delithiation, particle cracking, and conductive contact failure.
[0026] According to embodiments of this application, the region where the cobalt concentration gradually decreases can extend inward from the outer surface of the core to a depth of 20-500 nm. As the depth from the outer surface of the core increases, the concentration of cobalt in the corresponding region gradually decreases. This allows for the construction of a continuous electron transport network, promoting the release of active lithium, while also maintaining a high lithium replenishment capacity.
[0027] In this paper, the gradual decrease in cobalt concentration should be interpreted broadly, meaning that the concentration of cobalt decreases along the direction from the core surface towards the core center; this could be a linear decrease, a gradient decrease, etc. The relative content change trend of cobalt along the depth direction can be obtained by XRD testing of samples at different etching depths.
[0028] According to an embodiment of this application, the XRD pattern of the composite lithium supplement contains a first diffraction peak and a second diffraction peak. The 2θ of the first diffraction peak is located between 23.38° and 23.58°, and the 2θ of the second diffraction peak is located between 44.1° and 47.5°. The ratio of the peak intensity I1 of the first diffraction peak to the peak intensity I2 of the second diffraction peak is P1 = I2 / I1, and satisfies: 1.2% ≤ P1 ≤ 5%. Specifically, P1 can be 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, 4.8%, 5.0%, or any two of these values. Specifically, the first diffraction peak corresponds to the strongest peak of the core, and the second diffraction peak corresponds to the strongest peak of cobalt. The ratio of their peak intensities is within the above range, which can both construct a continuous electron transport network to promote the release of active lithium and also take into account a high lithium replenishment capacity.
[0029] According to an embodiment of this application, P1 gradually decreases in the direction from the core surface to the core center. This better promotes the gradient distribution of elemental cobalt, improving the release of active lithium while also increasing lithium replenishment capacity.
[0030] According to embodiments of this application, the mass ratio of the core to the carbon coating layer is 100:(1~4), specifically 100:1, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, or any two of these ranges. In other words, based on the mass of the core, the mass fraction of the first coating layer is 1wt%~4wt%. Within this range, a good ion transport network can be constructed, while side reactions can be effectively suppressed.
[0031] According to embodiments of this application, the metal oxide includes Li m MO (m+n) / 2 M includes Al and / or Mn, 0 ≤ m ≤ 2, 2≤n≤4. It can be understood that in the above chemical formula, n is the average valence state of M, and m is the Li content normalized to each M atom.
[0032] In some embodiments, the metal oxide includes at least one selected from Al2O3, LiAlO2, MnO, Mn2O3, Mn3O4, MnO2, LiMnO2, Li2MnO3, and LiMn2O4. Specifically, lithium-containing metal oxides such as LiAlO2, LiMnO2, Li2MnO3, and LiMn2O4 are formed by the in-situ reaction of Al2O3 or manganese oxide with residual lithium source on the surface of the lithium replenishing agent during heat treatment. The second coating layer formed by the metal oxide can, on the one hand, consume or fix residual active lithium on the material surface, reducing the generation of residual alkalis such as LiOH and Li2CO3, thereby improving the slurry processing adaptability of the material and reducing subsequent gas generation; on the other hand, aluminum-based oxides have good chemical inertness and interfacial stabilizing effects, which can suppress surface side reactions, while manganese-based oxides have certain lithium-ion transport capabilities and structural compatibility with the cathode system, which can buffer the interfacial stress during the delithiation process to a certain extent. Thus, the composite interface structure of "conductive buffer layer and stable protective layer" formed by the second coating layer and the inner first coating layer not only retains the promoting effect of the carbon coating layer on the delithiation kinetics and electron transport of the composite lithium replenishing agent, but also improves the chemical stability of the outer surface.
[0033] According to embodiments of this application, the mass ratio of the core to the second coating layer is 100:(0.13~3.78), specifically 100:0.13, 100:0.2, 100:0.5, 100:0.8, 100:1, 100:2, 100:3, 100:3.78, or any range between two of these. In other words, based on the mass of the core, the mass fraction of the second coating layer is 0.13wt%~3.78wt%. This effectively suppresses residual alkali formation, improves the slurry processing adaptability of the material, reduces subsequent gas generation, and enhances delithiation kinetics and interface stability.
[0034] According to an embodiment of this application, the XRD pattern of the composite lithium supplement contains a third diffraction peak, which is the strongest peak among the diffraction peaks with 2θ located between 21.2°~22.7°, 34.2°~35.7°, 44.9°~46.9°, 56.1°~67.7°, 15.0°~15.8°, 18.1°~18.9°, 31.6°~36.6°, and 39.8°~41.3°; the ratio of the peak intensity I3 of the third diffraction peak to the peak intensity I1 of the first diffraction peak is P2=I3 / I1, and satisfies: 0<P2≤3.5%, where P2 can specifically be 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, or any two of them. Specifically, the third diffraction peak corresponds to the strongest peak in the metal oxide diffraction peaks, and its peak intensity ratio with the first diffraction peak meets the above requirements. This can effectively suppress the formation of residual alkali, improve the slurry processing adaptability of the material and reduce subsequent gas generation, and also improve the delithiation kinetics and interface stability.
[0035] According to embodiments of this application, the coating coverage of the composite lithium supplement is 80%~95%, specifically 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 95%, or any range between two of these. Therefore, uniform coating effectively improves the storage stability of the composite lithium supplement.
[0036] According to embodiments of this application, the particle size D of the composite lithium supplement is... v50 The particle size ranges from 6.0 μm to 16.0 μm, specifically from 7.0 μm to 14.0 μm. As a specific example, the particle size D of the composite lithium supplement... v50The particle size ranges from 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, 16.0 μm, or any two of these ranges. Therefore, when the particle size of the composite lithium replenisher is within these ranges, the lithium-ion transport distance is suitable, making it easier for lithium ions to be extracted and achieving a higher lithium replenishment capacity.
[0037] According to an embodiment of this application, the specific surface area of the composite lithium supplement is 0.3 m². 2 / g~1.8 m 2 / g, specifically 0.4 m 2 / g~1.5 m 2 / g. As a specific example, the specific surface area of the composite lithium supplement is 0.3 m². 2 / g, 0.5 m 2 / g, 0.8 m 2 / g, 1.0 m 2 / g, 1.2 m 2 / g, 1.5 m 2 / g, 1.8 m 2 / g or any two of these values. This facilitates the extraction of active lithium and promotes the full utilization of the lithium replenishment capacity of the composite lithium replenishing agent.
[0038] According to an embodiment of this application, the compaction density of the composite lithium supplement is 1.7 g / cm³. 3 ~2.1 g / cm 3 Specifically, it is 1.9 g / cm³. 3 ~2.0 g / cm 3 As a specific example, the compaction density of the composite lithium supplement is 1.7 g / cm³. 3 1.8 g / cm 3 1.9 g / cm 3 2.0 g / cm 3 2.1 g / cm 3 Or a range between either or both. Therefore, composite lithium replenishing agents exhibit high lithium replenishment capacity.
[0039] According to an embodiment of this application, the first-week charge specific capacity of the composite lithium replenisher is 800 mAh g. -1 ~950 mAhg -1 Specifically, such as 800 mAh g -1 820 mAh g -1 840 mAh g -1 860 mAh g -1 880 mAh g -1900 mAh g -1 920 mAh g -1 940 mAh g -1 950 mAh g -1 Or a range between either or both. This can effectively improve the battery's first-week charge specific capacity and enhance its overall performance.
[0040] According to embodiments of this application, the composite lithium replenishing agent, under conditions of 25℃±1℃ and 15%±2% relative humidity, retains a capacity of 80%~99% after 4 hours, specifically within the ranges of 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 99%, or any two of these ranges. This effectively improves the cycle life of the battery.
[0041] A second aspect of this application provides a method for preparing the aforementioned composite lithium supplement. According to an embodiment of this application, the method includes: mixing a lithium source and a cobalt source in a stoichiometric ratio, and performing a first sintering under an inert atmosphere to obtain a first sintered product; mixing the first sintered product with a carbon source, and performing a second sintering under an inert or reducing atmosphere to form a first coating layer on the surface of the first sintered product to obtain a second sintered product; mixing the second sintered product with a metal oxide source, and performing a third sintering under an inert atmosphere to form a second coating layer on the surface of the second sintered product to obtain a composite lithium supplement; wherein the second sintering includes a first holding stage and a second holding stage, wherein the holding temperature of the first holding stage is 300°C to 500°C; and the holding temperature of the second holding stage is 550°C to 700°C. In this method, the second sintering through segmented sintering can induce controlled reduction of the surface layer of the first sintering product and generate cobalt in situ, resulting in a composite lithium supplement with better overall performance. Moreover, the operation is simple and convenient, highly compatible with existing processes, and easy to achieve large-scale production. The resulting composite lithium supplement has higher lithium supplementation capacity and chemical stability.
[0042] According to embodiments of this application, the lithium source may include at least one of lithium hydroxide, lithium oxide, lithium carbonate, and lithium chloride; the cobalt source may include at least one of cobalt oxide and cobalt hydroxide; the molar ratio of lithium in the lithium source to cobalt in the cobalt source is 5.7:1 to 6.3:1 (specifically, such as 5.7:1, 5.8:1, 5.9:1, 6.0:1, 6.1:1, 6.2:1, 6.3:1, or any range between two of them). Therefore, a core with superior performance can be effectively prepared.
[0043] According to embodiments of this application, in each step of the method, the mixing is carried out using a high-speed mixer or hummingbird resonance. This ensures uniform mixing of the raw materials, facilitating the acquisition of a composite lithium supplement with superior performance. As an example, mixing is performed using hummingbird resonance, which further improves mixing uniformity. In some embodiments, the frequency of the hummingbird resonance can be 55 Hz, the acceleration can be 40 G~100 G, and the resonance time can be 20 min~80 min. This allows for highly efficient and uniform mixing.
[0044] According to embodiments of this application, the inert atmosphere used in the first sintering process includes at least one of nitrogen or argon. This ensures a smooth reaction and reduces raw material costs.
[0045] According to embodiments of this application, the equipment used for the first sintering can be a tube furnace, a box furnace, a pusher kiln, or a roller kiln. This results in a better sintering effect.
[0046] According to an embodiment of this application, the first sintering temperature is 500℃~1000℃, specifically 500℃, 600℃, 700℃, 800℃, 900℃, 1000℃, or any two of these ranges. Within this temperature range, the lithium source and cobalt source can react quickly and fully to obtain the first sintered product, with fewer side reactions.
[0047] According to an embodiment of this application, the first sintering time is 8h to 24h, specifically 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, or any range between two of these. This time allows the reaction to proceed fully without wasting time and energy due to excessively long reaction times.
[0048] According to embodiments of this application, after the first sintering is completed, the process may further include crushing and sieving the first sintered product. In some embodiments, the crushing method includes at least one of ball milling, sand milling, air jet milling, and colloid milling; sieving may be performed using a 200-400 mesh sieve.
[0049] According to embodiments of this application, the carbon source includes at least one of acetylene black, carbon nanotubes, and Ketjen black. This allows for the formation of a carbon coating layer with good encapsulation effect, improving the conductivity of the composite lithium supplement, enhancing interface stability, and inducing the reduction of cobalt in the core to elemental cobalt.
[0050] According to embodiments of this application, in this step, the mixing is carried out using a high-speed mixer or hummingbird resonance. This ensures uniform mixing of the raw materials, facilitating the acquisition of a composite lithium supplement with superior performance. As an example, mixing is performed using hummingbird resonance, which further improves mixing uniformity. In some embodiments, the frequency of the hummingbird resonance can be 55 Hz, the acceleration can be 40 G~100 G, and the resonance time can be 20 min~80 min. This allows for highly efficient and uniform mixing.
[0051] According to an embodiment of this application, in the second sintering, the holding temperature of the first holding stage is 300℃~500℃ (specifically, 300℃, 320℃, 350℃, 380℃, 400℃, 420℃, 450℃, 480℃, 500℃ or any two of these ranges), and the holding time of the first holding stage is 1h~3h (specifically, 1h, 1.5h, 2.0h, 2.5h, 3h or any two of these ranges); the holding temperature of the second holding stage is 550℃~700℃ (specifically, 550℃, 580℃, 600℃, 620℃, 650℃, 680℃, 700℃ or any two of these ranges); and the holding time of the second holding stage is 4h~8h (specifically, 4h, 5h, 6h, 7h, 8h or any two of these ranges). The first heat preservation stage can promote the adhesion, spreading and interfacial contact of carbon source on the meshing surface, while the second heat preservation stage can effectively induce controlled reduction of the surface layer of the first sintering product and generate cobalt element in situ.
[0052] Furthermore, as the second holding stage proceeds, the active oxygen and / or lattice oxygen on the outer surface of the first sintered product are preferentially consumed by the carbon source, resulting in a low oxidation potential region on the outer surface of the first sintered product. Under continuous holding conditions, oxygen in the grain boundaries, defect regions, and near-surface lattice near the outer surface of the first sintered product migrates further outward and is consumed, causing the reduction-affected region to gradually extend from the outer surface of the first sintered product towards its center. This leads to the gradual reduction of Co species in the near-surface region to elemental cobalt, thereby allowing the elemental cobalt concentration to gradually decrease from the core surface towards the core center. Furthermore, by controlling the temperature and time of the second holding stage within the aforementioned range, the depth of the reduction-affected region extending into the interior of the first sintered product can be controlled.
[0053] According to embodiments of this application, the inert atmosphere used in the second sintering includes at least one of nitrogen or argon. This ensures a smooth reaction and reduces raw material costs.
[0054] According to embodiments of this application, the equipment used for the second sintering can be a tube furnace, a box furnace, a pusher kiln, or a roller kiln. This results in a better sintering effect.
[0055] According to embodiments of this application, after the second sintering is completed, the process may further include crushing and sieving the second sintered product. In some embodiments, the crushing method includes at least one of ball milling, sand milling, air jet milling, and colloid milling; sieving may be performed using a 200-400 mesh sieve.
[0056] According to embodiments of this application, the metal oxide source includes at least one of an aluminum source and a manganese source, preferably the aluminum source includes Al2O3, and the manganese source includes at least one of MnO, Mn2O3, Mn3O4, and MnO2. This effectively forms a metal oxide coating layer, improving the interfacial stability of the composite lithium supplement.
[0057] According to an embodiment of this application, the third sintering temperature is 300℃~700℃ (specifically, 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, or any two of these ranges); the third sintering time is 5h~10h (specifically, 5h, 6h, 7h, 8h, 9h, 10h, or any two of these ranges). This allows for the formation of a second coating layer with good coverage and strong adhesion.
[0058] According to embodiments of this application, the inert atmosphere used in the third sintering process includes at least one of nitrogen or argon. This ensures the smooth progress of the reaction and reduces raw material costs.
[0059] According to embodiments of this application, the equipment used for the third sintering can be a tube furnace, a box furnace, a pusher kiln, or a roller kiln. This results in a better sintering effect.
[0060] According to embodiments of this application, after the third sintering is completed, the process may further include crushing and sieving the third sintering product. In some embodiments, the crushing method includes at least one of ball milling, sand milling, air jet milling, and colloid milling; sieving may be performed using a 200-400 mesh sieve.
[0061] In a third aspect, this application provides a positive electrode sheet. According to embodiments of this application, the positive electrode sheet includes the aforementioned composite lithium replenishing agent. When used in a battery, this positive electrode sheet exhibits a high initial charge specific capacity and a long cycle life.
[0062] According to an embodiment of this application, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side surface of the positive current collector. The positive active material layer includes the composite lithium supplement agent, positive electrode material, positive conductive agent and positive electrode binder mentioned above.
[0063] According to embodiments of this application, the positive current collector can be a metal current collector or a composite current collector. Metal current collectors include at least one of aluminum foil current collectors and carbon-coated aluminum foil current collectors; composite current collectors may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. Composite current collectors can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0064] According to embodiments of this application, the cathode material includes one or more of lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium cobalt phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, and lithium-rich layered oxides. In some embodiments, the aforementioned composite lithium supplementer can be directly used as the cathode material.
[0065] According to embodiments of this application, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0066] According to embodiments of this application, the positive electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0067] In a fourth aspect, this application provides a battery. According to embodiments of this application, the battery includes the aforementioned composite lithium replenishing agent or the aforementioned positive electrode sheet. This battery exhibits a high initial charge specific capacity and a long cycle life.
[0068] According to an embodiment of this application, the battery may include the aforementioned positive electrode, negative electrode, electrolyte, and separator. The positive electrode, negative electrode, and separator are all immersed in the electrolyte. During the charging and discharging process of the battery, active ions are inserted and extracted back and forth between the positive and negative electrodes. The electrolyte plays the role of conducting ions between the positive and negative electrodes. The separator is disposed between the positive and negative electrodes, mainly to prevent short circuits between the positive and negative electrodes, while allowing active ions to pass through.
[0069] According to an embodiment of this application, the battery can be a solid-state battery, in which case the battery can include the positive electrode, negative electrode and solid electrolyte membrane described above, wherein the solid electrolyte membrane is disposed between adjacent positive electrode and negative electrode.
[0070] According to an embodiment of this application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located at least on one side of the negative electrode sheet. The negative electrode active material layer may include a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder.
[0071] According to embodiments of this application, the negative electrode current collector includes copper foil, composite copper foil, etc.
[0072] According to embodiments of this application, the negative electrode active material may include carbon-based materials (such as artificial graphite), silicon-based materials, tin-based materials, etc. In some embodiments, lithium foil can be directly used as the negative electrode material.
[0073] According to embodiments of this application, the negative electrode binder includes at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0074] According to embodiments of this application, the negative electrode conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0075] According to embodiments of this application, the diaphragm includes polyethylene diaphragm, polypropylene diaphragm, polyethylene / polypropylene composite diaphragm, etc.
[0076] A fifth aspect of this application provides an electrical device. According to embodiments of this application, the electrical device includes the aforementioned composite lithium replenisher, the aforementioned positive electrode, or the aforementioned battery.
[0077] It is understood that there are no particular restrictions on the specific type of electrical device, and it can be any device that uses a battery as a power source or energy storage unit. As examples, electrical devices include, but are not limited to, electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), mobile terminals (such as mobile phones, laptops, game consoles, wearable devices, etc.), drones, aerospace equipment, satellites, ships, energy storage systems, and so on.
[0078] It is understandable that, in addition to the battery mentioned above, the electrical device also includes necessary structures and components, all of which can be made with reference to conventional technologies. For example, an electric vehicle may include a body, chassis, tires, navigation system, radar system, steering system, braking system, lubrication system, cooling system, driving system, etc., which will not be described in detail here.
[0079] The embodiments of this application are described in detail below.
[0080] Example 1: Preparation of composite lithium supplement: (1) Weigh Li2O and CoO in a molar ratio of 3:1, mix them evenly using a high-speed mixer, and then perform the first sintering at 700°C under a nitrogen atmosphere for 12 hours. (2) The product obtained above was crushed by air jet milling and sieved through a 400-mesh sieve to obtain the first sintered product with the chemical formula Li6CoO4. (3) Weigh the first sintered product and Ketjen black at a mass ratio of 1:0.02, mix them using a hummingbird resonance device at a frequency of 55Hz, a mixing acceleration of 80G, and a mixing time of 40min. After mixing, keep the mixture at 400℃ for 2h under a nitrogen atmosphere, and then keep it at 600℃ for 6h. (4) The product obtained above is crushed by air jet milling and sieved through a 400-mesh sieve to obtain a second sintered product with a carbon coating on the surface of the core and cobalt in the core. (5) Weigh the above second sintered product and Mn3O4 at a mass ratio of 1:0.0056, mix them using a hummingbird resonance device at a frequency of 55Hz, a mixing acceleration of 80G, and a mixing time of 40min, and then sinter them for 6h in a nitrogen atmosphere at 600℃. (6) The product of the third sintering above is crushed by air jet milling and sieved through a 400-mesh sieve to obtain a composite lithium supplement.
[0081] Preparation of positive electrode: The composite lithium supplement, positive electrode conductive agent Super P, and positive electrode binder polyvinylidene fluoride obtained above are mixed in a mass ratio of 80:10:10, and then mixed with solvent NMP to obtain a positive electrode slurry. The positive electrode slurry is coated on the surface of aluminum foil, and after drying, rolling and slicing, a positive electrode sheet is obtained.
[0082] Preparation of negative electrode: The negative electrode uses a lithium metal sheet with a diameter of 18mm.
[0083] Battery assembly: The separator is a ceramic particle-modified polyethylene (PE) microporous membrane; the electrolyte includes ethylene carbonate (EC), diethyl carbonate (DEC), and LiPF6, wherein the volume ratio of ethylene carbonate (EC) to diethyl carbonate (DEC) is 3:7, and the concentration of LiPF6 is 1 mol / L. The above positive electrode, negative electrode, separator, and electrolyte are assembled to obtain a lithium battery.
[0084] Example 2-13 Same as Example 1, with specific differences shown in Table 1.
[0085] Comparative Example 1 Same as Example 1, except that only steps (1) and (2) are performed, and the first sintered product is directly used as a lithium supplement. Other parameter differences are shown in Table 1.
[0086] Comparative Example 2 Same as Example 1, except that steps (3) and (4) are not performed, so that the core does not contain elemental cobalt. Other parameter differences are shown in Table 1.
[0087] Comparative Example 3 Same as Example 1, except that: the oxide coating layer is located between the core and the carbon coating layer. Specifically, the first sintering product obtained in step (2) is directly subjected to steps (5) and (6), and then the product obtained in step (6) is subjected to steps (3) and (4). Other parameter differences are shown in Table 1.
[0088] Comparative Example 4 Same as Example 1, but with specific parameter differences shown in Table 1.
[0089] Table 1
[0090] Performance testing: 1. P1, P2: The sample to be tested was placed in the sample trough, compacted, and leveled. A Rigaku powder X-ray diffractometer (Smartlab 9kW) was used, with a Cu target wavelength (1.5418462Å), tube voltage of 40kV, tube current of 200mA, scanning speed of 10° / min, and scanning range of 10°~90°. A one-dimensional detector (1D) was used for measurement. Specific test conditions were: operating temperature: 21±5℃, humidity: <65%; cooling water circulator: temperature: 23±1℃, water pressure: 0.36 MPa; high pressure refrigerant: 0.8 MPa~1.8MPa, low pressure refrigerant: 0.4 MPa~0.7 MPa; step size: 0.0200°. The peak intensities of the first, second, and third diffraction peaks were read from the detected XRD pattern, and the relative peak intensity ratios P1 and P2 were calculated.
[0091] 2. Cobalt Concentration: Characterization was performed using XPS etching combined with XRD testing. Specifically, the composite lithium supplement powder was pressed into a powder sheet, which was then ion-etched for different durations. The etching time was converted into etching depth according to a pre-calibrated etching rate. The etching rate was related to the ion source type, ion energy, beam current intensity, and material type. Subsequently, samples with etching depths of 100 nm, 200 nm, and 500 nm were selected for XRD testing to compare the peak intensity ratio changes between the second and first diffraction peaks.
[0092] 3. Core: First Coating Layer: The test method for the mass ratio of the first coating layer to the core is to determine the carbon content of the lithium-supplementing additive using a high-frequency infrared carbon-sulfur analyzer, and calculate the weight of conductive carbon based on the mass of the tested sample; the lithium-supplementing additive is digested using an acid hydrolysis method, and the Co content is determined using ICP-OES, and the weight of conductive carbon is calculated based on the Li... a The core mass was calculated based on the theoretical mass fraction of Co in CoO4; each sample was tested in parallel at least 3 times, and the average value was taken. The mass ratio of the core to the first coating layer was then calculated.
[0093] 4. Core: Second Coating Layer: The lithium-supplementing additive is digested using acid hydrolysis, and the mass content of Co and M elements is determined by ICP-OES, based on Li... a The core mass is calculated based on the theoretical mass fraction of Co in CoO4; the phase composition of the second coating layer is confirmed by the measured XRD, and the mass of the second coating layer is calculated based on the theoretical mass fraction of M in the phase. Each sample is tested in parallel at least 3 times, and the average value is taken. Then the mass ratio of the core to the second coating layer is calculated.
[0094] 5. Coating Coverage: The sample was characterized using scanning electron microscopy combined with X-ray energy dispersive spectroscopy to obtain images of the distribution of coating elements on the particle surface. Ten non-overlapping fields of view were selected at equal intervals along the X and Y directions of the sample stage, with a distance of no less than 100 μm between the centers of adjacent fields of view. Particles located at the image edges, exhibiting significant overlap, or whose boundaries were indistinguishable due to aggregation were excluded during the statistical analysis. Scanning electron microscopy images and surface distribution images of coating feature elements were acquired for each field of view. The results were imported into ImageJ image analysis software. Based on the scanning electron microscopy images, the two-dimensional projection contours of the particles were delineated, and the total two-dimensional projection area of the counted particles was denoted as A. total The surface distribution intensity maps of C and M elements are converted into grayscale images, and binarization is performed using the Otsu automatic thresholding method. Regions exceeding the corresponding thresholds within the two-dimensional projection area of the particles are identified as C and M element signal regions, respectively. A union operation is performed on the area covered by the coating layer, and the resulting area is denoted as A. M+C The resulting sample coating coverage rate was A. M+C / A total ×100%.
[0095] 6. D v50 Take an appropriate amount of the sample to be tested and add it to the dry sample feeding system of the laser particle size analyzer (Mastersizer3000). Under the set dispersion pressure and vibration feeding conditions, the sample is uniformly dispersed and passed through the test area for detection. Record the particle size distribution curve of the sample.
[0096] 7. Specific surface area: Measured using a Micromeritics Tristar 3020 surface analyzer. The procedure may include: gradually adding N2 to the test material (after pre-removing physically adsorbed components) under vacuum conditions in the testing apparatus; calculating the pressure change caused by N2 adsorption using the constant volume method; and determining the amount of N2 adsorbed according to the gas equation. This yields the amount of N2 adsorbed from 0 atm to 0.3 atm at liquid nitrogen temperature, which is then converted into specific surface area per unit weight.
[0097] 8. Compacted density: Weigh 4g of the powder to be tested and add it to a mold with an inner diameter of 20mm. Compact it under a pressure of 20 KN and hold the pressure for 30 minutes. Then test the sample thickness using Powder Loresta software and generate a compacted density report.
[0098] 9. First-week charging specific capacity, capacity retention rate after 4 hours of storage at 25℃±1℃ and relative humidity of 15%±2%: (1) Prepare a coin cell with a fresh lithium replenishing electrode according to the specific preparation method of the coin cell described above. Place the assembled coin cell at 25°C with 25 mA g. -1 The current density was used for charge-discharge cycles, with an electrochemical window of 2.0V~4.5V. The charge-discharge curve of the first cycle was recorded using Xinwei testing software to obtain the charge specific capacity C1 of the first cycle. (2) Weigh the predetermined mass of the powder to be tested, place it in air with a relative humidity of 15%±2% for 4 hours, and then take it out. Prepare a coin cell with an air-exposed lithium replenishment electrode according to the specific preparation method of the coin cell described above. Place the assembled coin cell at 25°C with 25 mA g -1 The current density was used for charge-discharge cycles, with an electrochemical window of 2.0V~4.5V. The charge-discharge curve of the first cycle was recorded using Xinwei test software to obtain the first cycle charge specific capacity C2. (3) The capacity retention rate of the lithium supplement to be tested is C2 / C1×100%.
[0099] Table 2
[0100] As can be seen from the examples and comparative data in Table 2, the composite lithium replenisher consists of a core, a carbon coating, and a metal oxide coating layer from the inside out. The first-week charging specific capacity and the capacity retention rate after 4 hours of storage at 25℃±1℃ and a relative humidity of 15%±2% are significantly improved.
[0101] Comparing Example 13 with Examples 1-12, it can be seen that the elemental cobalt is distributed in a gradient from the outer surface to the inside, and the battery's first-week charge specific capacity and capacity retention rate after 4 hours at 25℃±1℃ and relative humidity of 15%±2% are significantly better.
[0102] Comparing Comparative Example 1 and Examples 1-13, it can be seen that without a coating layer, the performance of the composite lithium replenisher is significantly deteriorated. Comparing Comparative Example 2 and Examples 1-13, it can be seen that without cobalt in the core and without a carbon coating layer, an effective conductive network cannot be formed, and the battery's first-week charge specific capacity and capacity retention rate after 4 hours at 25℃±1℃ and 15%±2% relative humidity are significantly reduced. Comparing Comparative Example 3 and Examples 1-13, it can be seen that when the positions of the first coating layer and the second coating layer are interchanged, the overall performance of the composite lithium replenisher is significantly reduced, indicating that only when carbon coating is inside and oxide coating layer is outside can they work together better to improve the overall performance of the composite lithium replenisher.
[0103] Comparing Comparative Example 4 and Examples 1-13, it can be seen that the second sintering temperature affects the formation of elemental cobalt. If the temperature is too low, elemental cobalt cannot be formed during the preparation process, and the overall performance of the composite lithium supplement will decrease significantly.
[0104] In the description of this invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0105] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0106] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A composite lithium supplement, characterized in that, include: The kernel comprises LiaCoO4 and elemental cobalt, 5.7 ≤ a ≤ 6.3; A covering layer, the covering layer covering at least a portion of the surface of the core, and including a first covering layer and a second covering layer, the first covering layer being located between the core and the second covering layer; The first coating layer is a carbon coating layer, and the second coating layer includes a metal oxide.
2. The composite lithium supplement agent according to claim 1, characterized in that, The concentration of elemental cobalt gradually decreases in the direction from the surface of the core toward the center of the core.
3. The composite lithium supplement agent according to claim 1, characterized in that, The XRD pattern of the composite lithium supplement has a first diffraction peak and a second diffraction peak. The 2θ of the first diffraction peak is between 23.38° and 23.58°, and the 2θ of the second diffraction peak is between 44.1° and 47.5°. The ratio of the peak intensity I1 of the first diffraction peak to the peak intensity I2 of the second diffraction peak is P1 = I2 / I1, and satisfies: 1.2% ≤ P1 ≤ 5%.
4. The composite lithium supplement agent according to claim 3, characterized in that, P1 gradually decreases in the direction from the kernel surface toward the kernel center.
5. The composite lithium supplement agent according to claim 1, characterized in that, At least one of the following conditions must be met: The mass ratio of the core to the first coating layer is 100:(1~4); The mass ratio of the core to the second coating layer is 100:(0.13~3.78).
6. The composite lithium supplement agent according to claim 1, characterized in that, The metal oxide includes Li m MO (m+n) / 2 M includes Al and / or Mn, 0 ≤ m ≤ 2, 2≤n≤4; Preferably, the metal oxide includes at least one of Al2O3, LiAlO2, MnO, Mn2O3, Mn3O4, MnO2, LiMnO2, Li2MnO3, and LiMn2O4.
7. The composite lithium supplement agent according to claim 3, characterized in that, The XRD pattern of the composite lithium supplement shows a third diffraction peak, which is the strongest peak among the diffraction peaks with 2θ located between 21.2°~22.7°, 34.2°~35.7°, 44.9°~46.9°, 56.1°~67.7°, 15.0°~15.8°, 18.1°~18.9°, 31.6°~36.6°, and 39.8°~41.3°. The ratio of the peak intensity I3 of the third diffraction peak to the peak intensity I1 of the first diffraction peak is P2=I3 / I1, and satisfies: 0<P2≤3.5%.
8. The composite lithium supplement agent according to claim 1, characterized in that, At least one of the following conditions must be met: The coating coverage of the composite lithium supplement is 80%~95%; The particle size D of the composite lithium supplement v50 The thickness ranges from 6.0 μm to 16.0 μm, preferably from 7.0 μm to 14.0 μm; The specific surface area of the composite lithium supplement is 0.3 m². 2 / g~1.8 m 2 / g, preferably 0.4 m 2 / g~1.5 m 2 / g; The compaction density of the composite lithium supplement is 1.7 g / cm³. 3 ~2.1 g / cm 3 The preferred value is 1.9 g / cm³. 3 ~2.0 g / cm 3 .
9. The composite lithium supplement agent according to claim 1, characterized in that, At least one of the following conditions must be met: The first-week charging specific capacity of the composite lithium replenisher is 800 mAh g. -1 ~950 mAh g -1 ; The composite lithium replenishing agent retains 80%~99% of its capacity after being placed for 4 hours at a temperature of 25℃±1℃ and a relative humidity of 15%±2%.
10. A method for preparing the composite lithium supplement agent according to any one of claims 1 to 9, characterized in that, include: The lithium source and cobalt source are mixed in stoichiometric ratio and subjected to a first sintering under an inert atmosphere to obtain the first sintered product. The first sintered product is mixed with a carbon source and sintered again under an inert or reducing atmosphere to form a first coating layer on the surface of the first sintered product, thereby obtaining the second sintered product. The second sintered product is mixed with a metal oxide source and sintered in an inert atmosphere to form a second coating layer on the surface of the second sintered product, thereby obtaining a composite lithium supplement. The second sintering includes a first heat preservation stage and a second heat preservation stage, wherein the heat preservation temperature of the first heat preservation stage is 300℃~500℃; and the heat preservation temperature of the second heat preservation stage is 550℃~700℃.
11. The method according to claim 10, characterized in that, At least one of the following conditions must be met: The mixing is achieved through a high-frequency mixer or hummingbird resonance. The inert atmosphere includes at least one of nitrogen or argon; The temperature of the first sintering is 500℃~1000℃; The first sintering time is 8h~24h.
12. The method according to claim 10, characterized in that, At least one of the following conditions must be met: The heat preservation time for the first heat preservation stage is 1 hour to 3 hours; The heat preservation time for the second heat preservation stage is 4 to 8 hours.
13. The method according to claim 10, characterized in that, At least one of the following conditions must be met: The temperature of the third sintering is 300℃~700℃; The third sintering time is 5h~10h.
14. The method according to claim 10, characterized in that, At least one of the following conditions must be met: The lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, and lithium chloride; The cobalt source includes at least one of cobalt oxide and cobalt hydroxide; The molar ratio of lithium in the lithium source to cobalt in the cobalt source is 5.7:1 to 6.3:1; The carbon source includes at least one of acetylene black, carbon nanotubes, and Ketjen black. The metal oxide source includes at least one of an aluminum source and a manganese source, preferably the aluminum source includes Al2O3, and the manganese source includes at least one of MnO, Mn2O3, Mn3O4, and MnO2.
15. A positive electrode plate, characterized in that, The composite lithium supplement agent includes any one of claims 1 to 9.
16. A battery, characterized in that, Includes the composite lithium supplement agent according to any one of claims 1 to 9 or the positive electrode sheet according to claim 15.
17. An electrical device, characterized in that, It includes the composite lithium replenishing agent according to any one of claims 1 to 9, the positive electrode sheet according to claim 15, or the battery according to claim 16.